1966
DOI: 10.1080/00288233.1966.10429344
|View full text |Cite
|
Sign up to set email alerts
|

Bloat in cattle

Abstract: Apparatus for foam separation, and its application to the isolation of surface active components of rumen liquor, are described in detail. Preliminary results demonstrate that foam fractions of rumen liquor drawn prior to bloating, and non-bloating feeds of red clover, show differences in concentrations of non-acid lipid, fatty acid, and carbohydrate components that are not reflected in the rumen liquor samples themselves. Foam separation has been used to isolate saponins from rumen liquor.Yellow bubbles conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
1974
1974

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is significant that the critical temperature for C1 S fatty acids to spread from a solid surface into a surface film is approximately 18°c (Davies & Rideal 1961). It has been shown that C1 S free fatty acids were concentrated in foams derived from samples of rumen liquor taken before feeding from cattle which subsequently bloated when fed red clover (Laby & Weenink 1966); and that the free fatty acids were major components of the lipids that concentrated in foams generated ill vitro from rumen liquor of bloating animals (Jones 1972). These results suggest that lipids (C1S fatty acids) ,;Iso are involved in the formation of rumen foams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is significant that the critical temperature for C1 S fatty acids to spread from a solid surface into a surface film is approximately 18°c (Davies & Rideal 1961). It has been shown that C1 S free fatty acids were concentrated in foams derived from samples of rumen liquor taken before feeding from cattle which subsequently bloated when fed red clover (Laby & Weenink 1966); and that the free fatty acids were major components of the lipids that concentrated in foams generated ill vitro from rumen liquor of bloating animals (Jones 1972). These results suggest that lipids (C1S fatty acids) ,;Iso are involved in the formation of rumen foams.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been followed in previous papers in this series, in which the properties of foams derived from plant proteins, protozoal proteins, and salivary proteins have been investigated (Mangan 1959;Jones & Lyttleton 1969, 1972a To provide comparable information about foams derived from rumen liquor itself, this paper extends the work of Mangan (19'59) and Laby (1969) by studying these foams under a variety of conditions. The second approach, where surface-active agents in rumen fluid are isolated and studied, was initially followed by Laby & Weenink (1966). In this paper it has been developed by further analysis of the composition of rumen foams, and by the study of a fraction, isolated from rumen liquor, capable of generating foams very similar to those produced in vitro from rumen liquor.…”
Section: Introductionmentioning
confidence: 99%